An investigation of reading strategies employed by trainee teachers - Feryal Cubukcu (Penerbitan UKM, 2007)
Reading strategies vary from comparing and contrasting to organizing information, experimenting with grammar, forming mind mapping, making errors work for them, using linguistic knowledge of the first language in second language, using contextual cues and sentential relations, identifying the grammatical category of words, demonstrating sensitivity to a different word order, making intelligent guesses, examine illustrations and seeing similarities and dissimilarities in the text. This article focuses on the reading strategies of teacher trainees by presenting the results of the study conducted in a teacher-training department at a state university in Western Turkey. It highlights the importance of strategy training and why the strategies should be taught to enhance the reading of the learners